Mini-Review of Dehydrated Products: Nutritional Properties and Mineral Components of Freeze Dried Tropical Fruits - Mat, Siti Alyani; Zainol, Noor Azwani; Sarmidi, Mohamad Roji (International Journal of Biotechnology for Wellness Industries, 2018)
The purpose of dehydration process is to reduce moisture content to prolong shelf life, to promote convenience and at the same time to assist transportation of delicate and perishable products across long distances. Freeze drying is known as one of the best methods to retain quality compared to other dehydration processes. This is due to lower instances of rupture of the structure and minimal loss of nutrient. These parameters are important to consumers and also for the food industry. This mini-review compares methods of dehydration processes, as well as their advantages and disadvantages when used in combination with other technologies. Data compilation on nutritional properties and mineral components of tropical fruits, namely guava, pineapple, papaya and jackfruits which had underwent freeze drying technologies are also reviewed.